Impacto social y familiar generado por la transformación del rol tradicional de la mujer en Ecuador - Yunga Macas, Tania Gissella (My University, 2019)
The research work focuses on the analysis of the social and family impact generated by the transformation of the traditional role of women in Ecuador, which historically has been marked by primary activities related to the perpetuation of the species and cultural reproduction, in view of the elaboration of strategies that reinforce the social conscience regarding the incorporation of the gender principle that emphasizes the coexistence of men and women, based on equity and equality, as two elements that recognize the physiological and morphological differences, where they emphasize the capacities, skills and development opportunities acquired. The general objective is to determine the impact of new social relations as consequences of the family role of women in the equator, with the collection of information is referred to a qualitative analysis, the object of study for the construction of strategies of intervention. The research is managed with sustained theories with bibliographic references of scientific articles, which is why we worked with a qualitative approach, women have multiple facets and important contributions to society, with the proposal contributes to the debate of equality between men and women and will make possible the achievement of the proposed objectives.
El trabajo investigativo se centra en el análisis del impacto social y familiar generado por la transformación del rol tradicional de la mujer en ecuador, que históricamente ha estado marcado por actividades primarias relacionadas con la perpetuación de la especie y la reproducción cultural, en perspectiva de la elaboración de estrategias que refuercen la conciencia social referente a la incorporación del principio de género que enfaticen la convivencia de hombres y mujeres, basados en la equidad e igualdad, como dos elementos que reconocen las diferencias fisiológicas y morfológicas, donde resaltan las capacidades ,habilidades y oportunidades de desarrollo adquiridos. El objetivo general radica en determinar el impacto de las nuevas relaciones sociales como consecuencias del rol familiar de la mujer en el ecuador, con la recopilación de información se hace referencia a un análisis de forma cualitativa, el objeto de estudio para la construcción de estrategias de intervención. La investigación se maneja con teorías sostenidos con referencia bibliográfica de artículos científicos por lo que se trabajó con un enfoque cualitativo, las mujeres tienen múltiples facetas e importantes aportes a la sociedad, con la propuesta contribuye al debate de la igualdad entre hombres y mujeres y posibilitará la consecución de los objetivos propuestos.
Keywords: FAMILIA; IMPACTO SOCIAL; MUJER; ECUADOR